2023
DOI: 10.1002/adma.202210550
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorinated Covalent Organic Framework with Accelerated Oxygen Transfer Nanochannels for High‐Performance Zinc–Air Batteries

Abstract: The establishment of abundant three‐phase interfaces with accelerated mass transfer in air cathodes is highly desirable for the development of high‐rate and long‐cycling rechargeable zinc–air batteries (ZABs). Covalent organic frameworks (COFs) exhibit tailored nanopore structures, facilitating the rational tuning of their specific properties. Here, by finely tuning the fluorinated nanopores of a COF, a novel air cathode for rechargeable ZABs is unprecedentedly designed and synthesized. COF nanosheets are deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…2,24 Reasonable construction of the surface structure of a bifunctional electrocatalyst to optimize the triple-phase interface is particularly useful for accelerating oxygen transfer and exposing more catalytic active sites, thereby promoting efficient and durable operation. 22,48,93,94…”
Section: Design Strategy For Advanced Bifunctional Oxygen Electrocata...mentioning
confidence: 99%
See 2 more Smart Citations
“…2,24 Reasonable construction of the surface structure of a bifunctional electrocatalyst to optimize the triple-phase interface is particularly useful for accelerating oxygen transfer and exposing more catalytic active sites, thereby promoting efficient and durable operation. 22,48,93,94…”
Section: Design Strategy For Advanced Bifunctional Oxygen Electrocata...mentioning
confidence: 99%
“…For RZABs, both the ORR and OER at the cathode mainly occur at the solid-liquid-gas triple-phase interfaces where the oxygen reactant/evolution, electronic transportation, and the ionic conductor intersect. 48,93 The performance of the reaction interface is deeply dependent on the microenvironment of the electrocatalysts in the actual working environment. 2,22 The half-cell test generally employs a rotating disc electrode (RDE) or rotating ring-disc electrode (RRDE) to evaluate the catalytic properties, and these electrodes are conducive to enhancing mass transfer and eliminating concentration polarization for maximizing the inherent catalytic activity.…”
Section: Microscale Interfacial Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Li + transfer environment will be improved under the regulated electronic states, which can further elevate the electrochemical performance of LMB. [41,42] Thus, effectively optimizing electron structure by the D-A effect will provide a better platform to understand Li + migration. [43] Herein, nitro-modified COF is introduced and served as an ASEI to realize the target of dendrite-free, long-life LMBs.…”
Section: Introductionmentioning
confidence: 99%
“…in 2011, with its higher stability than imine-linked COFs and the chelating sites provided by abundant polar functional groups (amides), , hydrazone-linked COFs have gained popularity among researchers, mainly in the field of catalysis and heavy metal ion adsorption and detection or I 2 uptake . Recently, the applications of some new hydrazone-linked COFs in the field of sensing , and energy storage , have also been discovered, showing great application prospects. For instance, Yang and co-workers found that a series of macrocycle-derived COFs have highly photocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%